IP-10 Promotes Latent HIV Infection in Resting Memory CD4+ T Cells via LIMK-Cofilin Pathway - Wang, Zhuo; Yin, Xiaowan; Ma, Meichen; Ge, Hongchi; Lang, Bin; Sun, Hong; He, Sijia; Fu, Yajing; Sun, Yu; Yu, Xiaowen; Zhang, Zining; Cui, Hualu; et al. (Frontiers in Immunology, 2021)
A major barrier to HIV eradication is the persistence of viral reservoirs. Resting memory CD4+ T cells are thought to be a major viral reservoir, but the mechanism underlying their latent infection by HIV is poorly understood. Our results suggest that plasma IP-10 was elevated in HIV-infected individuals, which was positively correlated with HIV viral load and viral reservoir size. We are therefore investigated the role of IP-10 in the establishment of HIV reservoir. We found that IP-10, binding to CXCR3, enhanced latent HIV infection of resting memory CD4+ T cell. IP-10 facilitated HIV entry and DNA integration and promoted cofilin phosphorylation and actin polymerization. Moreover, LIM kinase inhibitor and actin inhibitor treatments abrogated IP-10-mediated enhancement of latent infection by HIV. These results indicate that IP-10 is a critical factor involved in latent HIV infection, therapeutic targeting of IP-10 is a potential strategy for abolishing latent HIV infection.